Key Success Factors in the Trust Metaphor Framework for Profit Sharing Contracts: A Literature Review - Kautsar Riza Salman; Arif Zeinfiki Djunaedi (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to explore key success factors in profit-sharing-based contracts. Profit-sharing-based contracts such as mudharabah and musharakah carried out by Islamic banks are the core of financing in Islamic banks because they are directly related to the productive sector. The impact of this type of financing is greater for the industrial world than that of buying and selling-based financing. However, the facts show that there has been a decrease in the performance of the percentage of profit-sharing-based financing during the 2019-2022 period, and conversely, buying and selling-based financing has increased. In addition, the total operating profit from profit-sharing-based financing has also decreased during the 2019-2022 period. Mudharabah financing is mainly carried out on the basis of trust that arises between the owner of the funds (shahibul maal) and the business manager (mudharib). This study uses a qualitative approach with a literature review in order to gain a comprehensive understanding of the key success factors in profit-sharing-based financing contracts. Key success factors that are deepened based on the trust metaphor include knowledge of the rights and obligations of mudharib and shahibul maal, honest reporting, monitoring, and guarantees. In fulfilling the Trust, each party is required to have adequate knowledge of their rights and obligations in mudharabah and musharakah contracts. The honest and adequate presentation of financial information is disclosed by mudharib with reference to relevant Sharia accounting standards such as PSAK 101, PSAK 105, and PSAK 106. This disclosure is a form of mudharib's responsibility to shahibul maal. Regular monitoring can be carried out by shahibul maal actively or passively. Guarantees can be applied in sharing-based financing contracts other than guarantees provided by mudharib. This study produces theoretical contributions to science in the field of Sharia accounting and practice, especially for practitioners in the Sharia banking industry.